Demographic Factors Influence the Laboratory Parameters in COVID 19 Patients - Experience from Tertiary Care Center in Islamabad - Sohail, Summaya (International Journal of Pathology, 2022)
Background: As the pandemic of COVID-19 spread in different part of world, reports show significant differences in disease presentation, clinical symptoms, and progression, treatment-response and intensive care admissions Objective: The aim is to study demographic parameters and to evaluate and compare various basic laboratory parameters according to age groups of PCR confirmed COVID-19 patients and statistically analyze its significance. Material and Methods: It is a cross sectional, prospective study of 3 months duration from April 2020 to 2020, Pakistan Institute of Medical Sciences. Results: 115 COVID-19 positive patients with moderate to severe symptoms were included in the study. Patients were divided into three groups based on their ages, less than 25 years, 25-50 years and more than 50 years. Distribution of SARS-CoV-2 patients showed male predominance and age gradient with only few cases in children. We found that laboratory parameters associated with worse prognosis as lymphopenia and hypoalbuminemia were more common in patients more than 50 years of age. Neutrophilia was more common in young patients. Deranged Neutrophil lymphocyte ratio NLR was observed in all three-age stratified groups Conclusion: Combining parameters as NLR and age can be a potential indicator of prognosis.